Characterization of multidrug-resistant potential pathogens isolated from milk and some dairy products in Egypt - Ashraf, Dina; Ombarak, Rabee A; Samir, Ahmed; Abdel Salam, Ayah B (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study aimed to explore the incidence and antimicrobial resistance (AMR) of Escherichia coli, Staphylococcus aureus, and Bacillus cereus in raw milk and some Egyptian dairy products, namely Kariesh cheese and rice with milk. Material and Methods: 112 samples (70 raw milk, 30 Kariesh cheese, and 12 rice with milk) were randomly collected from different districts in Cairo and Giza, Egypt. The samples were examined for E. coli, S. aureus, and B. cereus presence. The susceptibility of the obtained isolates was tested against 11 antimicrobials using the disk diffusion method, and further, the presence of AMR genes was examined. Results: The incidences of E. coli, S. aureus, and B. cereus were 69.64%, 12.5%, and 16.7% in the examined samples, respectively. The antibiogram indicated that E. coli isolates (n = 60) were resistant to gentamycin (73.33%), ampicillin (AM, 53.3%), and cefotaxime (CTX, 16.66%). Multidrug-resistant (MDR) E. coli strains (n = 5) were tested for β-lactams resistance genes. blaTEM was detected in all isolates, and two of them additionally carried blaCTX-M. Staphylococcus aureus isolates (n = 10) were resistant to AM (100%), followed by tetracycline (TE), CTX, and gentamycin (60% each). All MDR S. aureus strains (n = 4) carried blaZ and tetK, and three of them additionally carried aac (6’)-aph (2’’). Bacillus cereus isolates (n = 30) showed resistance to AM (100%), amoxicillin (20%), and TE (6.66%). bla and tetA genes were detected in all MDR B. cereus isolates (n = 6). Conclusion: Our findings denote the high incidence of potential health hazards in raw milk and some of its products and the existence of AMR bacteria, including MDR strains, which can cause human illnesses that are difficult to treat. J. Adv. Vet. Anim. Res., 10(2): 275–283, June 2023 http://doi.org/10.5455/javar.2023.j679